The Religious Aspect of the Concept of “Virtuous Man” in the Legacy of Al-Farabi - Baizhuma, Samet; Meirbayev, Bekzhan; Kurmanaliyeva, Ainura; Alikbayeva, Marzhan; Tutinova, Nurgul (Journal of Ecohumanism, 2025)
Today, the idea of a virtuous man in the legacy of Al-Farabi is one of the most topical challenges due to the constant changes in values. Above all, the intensive social development of our society places high demands on the formation of an active, creative personality. Thus, the analysis of theoretical research and the general concept of personality is considered in various scientific fields. A virtuous man is the result of moral education in socio-historical development. The formation of personality occupies an important place in the personal characterization; that is, it provides highly conscious forms of behavior and actions, forming the unity of all their relations with reality. This point of view has formed the basis of most study fields. The authors consider values oriented towards a virtuous man (motives and needs, aspirations and demands, virtue and mercy) based on the heritage of Al-Farabi. Thus, a virtuous man in the heritage of Al-Farabi is, firstly, an individual as a subject of social interaction and conscious action. Secondly, it is a systematic state of the individual, determined by their inclusion in social relations, and is the basis for the syncretism of religious education.